Answer:
True
Explanation:
For one-to-one function, we have for all x₁ and x₂, where x₁ ≠ x₂, then, f(x₁) ≠ f(x₂)
Which gives;
f
Where f(x₁) = y₁, the result of the inverse of the f⁻¹(y₁) = x₁
By definition the inverse of a one-to-one function, f⁻¹ is a distinctive function whose domain is given by f⁻¹(f⁻¹(x)) = x for the values of x in f
Therefore, for one-to-one functions, f⁻¹(f⁻¹(x₁)) = x₁
Where f⁻¹(x₁) = y₁, is the inverse or reverse of a function f(x₁), therefore, we have;
f⁻¹(y₁) = x₁
Which proves the statement that y = f(x) then x= f⁻¹(y).